VAX014 for instillation in subjects with nonmuscle-invasive bladder cancer - Lerner, Seth P.; Karsh, Lawrence Ivan; O'Donnell, Michael A.; Shore, Neal D.; Lotan, Yair; Tsuji, Shingo; Giacalone, Matthew (Journal of clinical oncology, 2022)
488 Background: VAX014 is a novel tumor targeted oncolytic agent for intravesical administration. It is comprised of recombinant bacterial minicells, that actively target a3b1 and a5b1 integrins expressed on NMIBC and deliver an active cytotoxic/oncolytic protein payload, perfringolysin O. VAX014 is being investigated for the intravesical treatment of NMIBC in an ongoing multi-center Phase 1 marker lesion trial in subjects with low grade Ta disease (NCT 03854721). Methods: Subjects with up to 5 pathologically confirmed TaG1 lesions ≥ 5mm but ≤ 15mm are eligible to receive six (6) weekly intravesical instillations of VAX014. Subjects with presence or history of high-grade bladder cancer are ineligible. Phase 1a will establish the MTD using a 3+3 design. After the DSMB establishes the RP2D, a Phase 1b expansion will use this dose to treat an additional 10 patients. Results: No serious adverse events or dose limiting toxicities have been recorded through two dose cohorts (3 + 3 design) and evidence of clinical response has been observed. Treatment related adverse events have been limited to Grade 1/2 hematuria, dysuria, and urgency. Preclinical studies indicate the pharmacodynamic activity of VAX014 following weekly intravesical administration to immune competent mice bearing bladder tumors is immune dependent and synergizes with systemic PD-L1 blockade to eliminate organ confined tumors and extravesical tumors. Surviving mice are capable of rejecting tumor rechallenge due to development of protective antitumor immunologic memory in response to therapy. Exploratory immunohistochemical target validation studies in bladder tumor biopsy specimens from subjects with more advanced stage tumors (T1-T3), indicate overexpression of VAX014's target integrins, a3b1 and a5b1, in most samples tested. Conclusions: These clinical and preclinical data support the further development of VAX014 for the intravesical treatment of NMIBC and set a foundation for combination therapy with systemically administered immune checkpoint blockade in subjects with advanced disease. Clinical trial information: NCT03854721.